Distribution and preliminary assessment of a rare fungus Hemileccinum depilatum (Boletales, Basidiomycota) in Ukraine - Heluta, V.P.; Assyov, B.; Hayova, V.P. (Український ботанічний журнал, 2019)
Hemileccinum depilatum ( Boletales, Basidiomycota) is currently known from Western and Central Europe, the
Mediterranean, the Balkan Peninsula, and Asia (Azerbaijan and Turkey). The fungus is rare throughout its range and is included
in the Red Lists in several European countries. In Ukraine, the species is known since 2006. Formerly, H. depilatum was found
on the South Coast of Crimea, in the Mountain Crimea, Western Forest-Steppe and the Carpathians. The species was recorded
only in five localities in three regions of Ukraine: Khmelnytsky, Transcarpathian, and the Autonomous Republic of Crimea.
Over the recent years, the fungus has been also reported from the following five regions: Cherkasy, Ivano-Frankivsk, Kyiv, Lviv,
and Ternopil. Thus, by now the total number of the species localities increased from 5 to 14. However, the number of records
grows due to additional data recently provided from field observations by amateur mycologists, rather than it can be considered
as a result of an increasing population trend of the fungus. Undoubtedly, H. depilatum is a rarely occurring species in Ukraine
and is to be protected. A preliminary assessment of the species at the national level using the IUCN criteria and categories is
provided. Today, the main threat to its existence is collection of the fruit bodies by local population. Therefore, it is proposed
to continue searching for new localities of the fungus and to protect those sites at least at the regional level, as well as to provide
public outreach, primarily through social networks, which nowadays bring together tens of thousands of amateur mycologists
in Ukraine. Hemileccinum depilatum (Boletales, Basidiomycota) трапляється у Західній та Центральній Європі, Середземномор'ї, на Балканському півострові, а також в Азії (Азербайджан і Туреччина). Скрізь він є рідкісним, у ряді країн Європи внесений до природоохоронних списків. В Україні він відомий з 2006 р. Гриб знаходили на Південному березі Криму, у Гірському Криму, Західному Лісостепу та Карпатах. До цього дослідження в Україні було відомо лише п'ять його місцезнаходжень, розташованих в Автономній Республіці Крим, Закарпатській і Хмельницькій областях. Упродовж останніх років гриб був зареєстрований ще у п'яти областях – Івано-Франківській, Київській, Львівській, Тернопільській і Черкаській, а кількість відомих локалітетів виду зросла з 5 до 14. Однак це збільшення пов'язане насамперед з широким залученням до пошуків даного виду мікологів-аматорів, а не є наслідком тенденції до збільшення чисельності гриба. Отже, H. depilatum є рідкісним в Україні видом і потребує охорони. Здійснено попередню оцінку виду на національному рівні із застосуванням критеріїв та категорій МСОП. На сьогодні головною загрозою для його існування є збір плодових тіл населенням. Тому пропонується продовжувати пошук нових місцезнаходжень цього рідкісного гриба, брати їх під охорону хоча б на регіональному рівні, а також здійснювати роз'яснювальну роботу з населенням, насамперед через соціальні мережі, які на сьогодні об'єднують в Україні десятки тисяч мікологів-аматорів.